The use of nitrogen-15 in microbial natural product discovery and biosynthetic characterization - Morgan, Kalindi D. (Frontiers in Microbiology, 2023)
This mini-review covers the use of nitrogen-15 in bacterial and fungal natural product discovery and biosynthetic characterization from to 1970-2022. Nitrogen is an important element in a number of bioactive and structurally intriguing natural products including alkaloids, nonribosomal peptides, and hybrid natural products. Nitrogen-15 can be detected at natural abundance utilizing two-dimensional nuclear magnetic resonance and mass spectrometry. Additionally, it is a stable isotope that can be added to growth media for both filamentous fungi and bacteria. With stable isotope feeding, additional two-dimensional nuclear magnetic resonance and mass spectrometry strategies have become available, and there is a growing trend to use nitrogen-15 stable isotope feeding for the biosynthetic characterization of natural products. This mini-review will catalogue the use of these strategies, analyze the strengths and weaknesses of the different approaches, and suggest future directions for the use of nitrogen-15 in natural product discovery and biosynthetic characterization.